Numbers and distribution of wild geese in the Netherlands, 1984-89, with special reference to weather conditions - Lok, Martin; van den Berg, Leo; Ebbinge, Barwolt; van Haperen, Anton; Philippona, Jules; Prop, Jouke; Azn, Arend Timmerman (Wildfowl, 1992)
This paper deals with numbers of geese counted in the Netherlands from autumn 1984 through spring 1989. This period brought maximum numbers for Taiga Bean Goose (33,000), Tundra Bean Goose (204,000), Pink-footed Goose (23,000), White fronted Goose (423,000) Greylag Goose (81,000), Canada Goose (1500), Barnacle Goose (138,000) and Dark-bellied Brent Goose (99,000). This means that the Netherlands regularly hosts entire or large proportions of populations of several species. Taken all species together, at least 700,000 to 900,000 geese spent part of their annual cycle in the Netherlands during 1984-89. Severe winters did not have a significant effect on population size through starvation or a diminished breeding success in the subsequent breeding seasons. The main effect of such winters was that the cold forced geese wintering east of the Netherlands westward. Depending on the snow situation and the species involved, the northern part of the country was often deserted by geese. The Delta area was then the main refuge. In general, the smaller and shorter-billed geese responded faster than the larger and stouter-billed geese upon the onset of severe weather.